English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-05-09 14:41:59 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

-x^2+x+12=x^2+9
-x^2+x^2+x+12=x^2+x^2+9
x+12=2x^2+9
x-x+12-12=2x^2-x+9-12
2x^2-x-3=0
(2x-3)(x+1)=0
x=3/2 or x=-1

2007-05-09 14:51:22 · answer #1 · answered by Dave aka Spider Monkey 7 · 0 0

-x^2 + x + 12 = x^2 - 9

x + 12 = 2x^2 - 9 // add x^2 to both sides

x + 21 = 2x^2 //add 9 to both sides

2x^2 - x - 21 = 0 // subtract x + 21 from both sides


(2x - 7) (x + 3) = 0 . .. // Factor

2x-7 = 0 .. ... .. or ... ... x+3=0
2x = 7 .. .. .. .. .. .. x = -3
x = 7/2
x = 3 1/2 . .. ..or . .. .x = (-3)

NOTE: Gud decided to do this " Factor By Grouping" so he decided to represent his " -x " by values to make grouping possible, or he expanded the -x ( he viewed -x as a result of two values). When he expanded his -x he represented this by the values of 6x - 7x which is -x ... ... just so you know you can represent a value by equivelent values.

D3M copied the problem incorrectly; therefore, his answer is wrong. Notice he has a +9 as the last term, when it should be (-9).

2007-05-09 22:36:36 · answer #2 · answered by Anonymous · 0 0

-x^2 + x + 12 = x^2 - 9
-2x^2 + x +21 = 0

2x^2 - x -21 = 0
2x^2 +6x - 7x -21 = 0
2x(x+3) - 7(x+3) = 0
(x+3)(2x-7)=0

x = -3
x = 7/2

2007-05-09 21:52:50 · answer #3 · answered by gudspeling 7 · 0 0

x=-21

2007-05-13 00:16:27 · answer #4 · answered by Anonymous · 0 0

gud is correct! -x=6x-7x He factored by grouping. Sub in the answers and you'll see who is correct.

2007-05-09 22:25:15 · answer #5 · answered by Isosceles 2 · 0 0

fedest.com, questions and answers